The Role of Patient Complaint Handling in Improving Healthcare Quality: A Field Study at Jazan General Hospital - Kingdom of Saudi Arabia 2025 - Mania, Hamad Mohammed; Daraaj, Mona Ali (Journal of medical and pharmaceutical sciences, 2025)
This study addressed the problem of increasing complaint indicators and the failure to utilize them as an opportunity for continuous improvement, examining four main dimensions: administrative, human, technical, and organizational. Therefore, this study aimed to identify the role of handling patient complaints across these dimensions (administrative, human, technical, and organizational) in improving the quality of healthcare. The study focused on Jazan General Hospital in the Kingdom of Saudi Arabia. To achieve this, the study employed a descriptive-analytical approach, starting from the main hypothesis: "There is no statistically significant role for effectively handling patient complaints (in all its dimensions) in raising the quality of healthcare at Jazan General Hospital." Data was collected using a questionnaire and open-ended interviews with two purposive samples selected from individuals who had previously submitted complaints between January 1, 2025, and June 30, 2025. The first sample consisted of 375 individuals who completed an online questionnaire. The second sample consisted of 25 individuals who participated in open-ended interviews. The study reached a number of conclusions, most notably: the results of the hypothesis testing demonstrated a statistically significant impact of all dimensions of patient complaint handling (administrative, human, technical, and organizational) on improving the quality of healthcare. This led to the rejection of all null hypotheses and the acceptance of the alternative hypotheses. The "technical aspect" dimension ranked first with a mean score of 4.01 and a high degree of agreement, indicating a strong belief among study participants that analyzing complaint data effectively contributes to identifying weaknesses and preventing the recurrence of problems. The results in the administrative dimension showed a weakness in communication with patients after their complaints were resolved, with this item receiving the lowest mean score (2.65).